THE USE OF DISCOURSE COMPLETION TASK (DCT) AS EXPLICIT INSTRUCTION ON INDONESIAN EFL LEARNERS’ PRODUCTION OF SUGGESTION ACTS - Aika Salsabila; Bahagia Saragih; Barli Kifli; Erika Novalia Srywina Sibuea; Khairiah Putri Zulfran; Lulu Olivia Simorangkir; Nabila Ramayani; Safira Abita (STKIP Subang, 2026)
This study aims to identify pragmatic strategies used by EFL students in peer communication, particularly in the speech acts of requesting, refusing, and apologizing. A descriptive quantitative method was applied using a Discourse Completion Task (DCT) instrument adapted from Blum-Kulka, House, and Kasper (1989). Ten students were selected as respondents through purposive sampling. The results indicate that EFL students tend to use Conventionally Indirect strategies in requesting and refusing situations, while in apologizing situations, students lean toward Softened Indirect to Full Apologetic strategies. These findings suggest that students possess adequate pragmatic awareness in maintaining politeness during informal peer communication.